2021
DOI: 10.1021/jacs.1c07771
|View full text |Cite
|
Sign up to set email alerts
|

Fast Fluoroalkylation of Proteins Uncovers the Structure and Dynamics of Biological Macromolecules

Abstract: Covalent labeling of proteins in combination with mass spectrometry has been established as a complementary technique to classical structural methods, such as X-ray, NMR, or cryogenic electron microscopy (Cryo-EM), used for protein structure determination. Although the current covalent labeling techniques enable the protein solvent accessible areas with sufficient spatial resolution to be monitored, there is still high demand for alternative, less complicated, and inexpensive approaches. Here, we introduce a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…The reagents utilized in these workflows and hence amino acid selectivity, reaction rates, and necessary considerations can vary widely. ,, , A concern of many labeling-based technologies is the influence derivatization has on the conformation of the protein. This is especially pertinent with these technologies, as many implementations generate multiply derivatized species and utilize reaction durations in the second to minute time scales.…”
Section: Introductionmentioning
confidence: 99%
“…The reagents utilized in these workflows and hence amino acid selectivity, reaction rates, and necessary considerations can vary widely. ,, , A concern of many labeling-based technologies is the influence derivatization has on the conformation of the protein. This is especially pertinent with these technologies, as many implementations generate multiply derivatized species and utilize reaction durations in the second to minute time scales.…”
Section: Introductionmentioning
confidence: 99%
“…For example, top-down hydrogen/deuterium exchange (HDX) indicated that extensive deuteration takes place at the intervening loops and in the F-region, and fast photochemical oxidation of proteins (FPOPs) revealed that helix F has the higher accessibility among all apomyoglobin peptides . In addition, the fast fluoroalkylation of proteins (FFAPs) revealed that the increased modification of aromatic amino acids situated at helix F was observed in apomyoglobin . Overall, this leads us to conclude that the region helix F encompassing fully tryptic peptides, GHHEAELKPLAQSHATK, is readily accessible for PK and is more flexible in apomyoglobin.…”
Section: Resultsmentioning
confidence: 94%
“…Since fully tryptic peptide GLSDGEWQQVLNVWGK (2–17) is in helix A, together these findings indicate that helix A has solvent accessibility, in line with the phenomenon that has been documented by HDX, FPOP, and FFAP. For example, HDX revealed that helix A is only marginally developed with deuteration levels around 0.8, and the FPOP data showed that the protein segment (GLSDGEWQQVLNVWGK) (2–17) located on helix A gains different levels of protection with respect to folding time, and modification on helix A was also observed by FFAP . Overall, each method can provide insight into the unique features of surface accessibility and flexibility .…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this obstacle, hydroxyl radicals were introduced utilizing dissociation of water molecules by synchrotron irradiation . Because the availability of synchrotron for footprinting experiments is rather limited, alternative methods have been successfully tested to generate hydroxyl radicals based on the photolysis of hydrogen peroxide. Later, other radicals were utilized as well to access the solvent-accessible surface area of proteins. …”
mentioning
confidence: 99%